Tenure, Divesity, and Commitment: Community Participation for Urban Service Provision - Lall, Somik V.; Deichmann, Uwe; Lundberg, Mattias K.A.; Chaudhury, Nazmul (World Bank, Washington, D.C., 2013)
What factors influence community participation in the delivery of urban services? In particular, does security of tenure enhance the probability of participation as it provides individuals with incentives to act collectively in pursuit of a common objective? And are collective efforts less likely to succeed when there is a high degree of heterogeneity in culture or endowments among community members? The authors use household level survey data for Bangalore, India, to show that tenure security has a significant impact on the willingness of residents to participate even when neighborhoods are diverse in terms of their cultural background and welfare status. Their findings suggest that participation is possible in heterogeneous communities when it is a means to a common objective and not a goal by itself.